The Protective Influence of Bilingualism on the Recovery of Phonological Input Processing in Aphasia After Stroke - De Letter, Miet; Cocquyt, Elissa-Marie; Cromheecke, Oona; Criel, Yana; De Cock, Elien; De Herdt, Veerle; Szmalec, Arnaud; Duyck, Wouter (Frontiers in Psychology, 2021)
Language related potentials are increasingly used to objectify (mal)adaptive neuroplasticity in stroke-related aphasia recovery. Using pre-attentive (mismatch negativity-MMN) and attentive (P300) phonologically-related paradigms, neuroplasticity in sensory memory and cognitive functioning underlying phonological processing can be investigated. In aphasic patients, MMN amplitudes are generally reduced for speech sounds with a topographic source distribution in the right hemisphere. For P300 amplitudes and latencies, both normal and abnormal results have been reported. The current study investigates the pre-attentive and attentive phonological discrimination ability in 17 aphasic patients (6 mono- and 11 bilinguals, age 41-71) at two timepoints during aphasia recovery. Between the two timepoints, a significant improvement of behavioral language performance in both languages is observed in all patients with the MMN-latency at timepoint 1 as a predictive factor for aphasia recovery. In contrast to monolinguals, bilingual aphasic patients have a higher probability to improve their processing speed during rehabilitation, resulting in a shortening of the MMN latency over time, which sometimes progresses towards the normative values.